Bibliometric and systematic review of library roles in early childhood Islamic education - Irawati, Sutiyah Nova; Nugroho, Prasetyo Adi; Anna, Nove Eka Variant; Irfana, Maisyatus Suadaa; B, Nurfarawahidah (Jurnal Kajian Informasi & Perpustakaan, 2025)
Background: Libraries in Islamic schools globally are increasingly recognized as dynamic learning environments. However, bibliometric evidence on their role in supporting early childhood Islamic education remains limited. Purpose: This study examines the role of libraries in advancing early childhood Islamic education, emphasizing their potential as dynamic centers of literacy, pedagogy, and moral formation. Methods: This study used Scopus-indexed metadata from 2008 to 2025 as samples. At least 217 documents were analyzed using bibliometric methods (VOSviewer and RStudio), and 64 papers were qualitatively reviewed. Results: The results showed that highly cited works emerged from diverse regions, reflecting a global perspective on Islamic pedagogy. Moreover, thematic trends highlighted teacher education, emotional intelligence, and parental involvement. The result also showed that early childhood was a critical stage for instilling Islamic values such as honesty (ṣidq), compassion (raḥmah), tolerance (tasāmuḥ), and discipline (inḍibāṭ). However, educators often faced challenges, including limited pedagogical innovation, inadequate school training, and restricted access to quality resources. To address these gaps, libraries could provide curated materials, facilitate professional development for teachers, and integrate interactive and technology-driven learning strategies. Conclusion: Libraries are not merely repositories but strategic facilitators of holistic child development by leveraging digital innovations such as AI to strengthen children’s literacy. Implication: The findings of this study imply that libraries can enhance community-based Islamic early-childhood education by providing curated resources and interactive programs for parents and teachers to foster children’s literacy and moral development.